Emergent linguistic scenarios at the border region Tijuana-San Diego - Toledo Sarracino, David Guadalupe (2018)
The following article is the first exploratory study, which has a main objective to understand the dynamics of migration in the current economic and social matters in Baja California; due to economic development and the demographic population grows in Tijuana a new linguistic mosaic has been incorporated.This first description will support other studies, specifically in the field of language planning and language policy at the border region (Tijuana-San Diego), as a beginning but at the same time other regions that experiment massive and accelerated migration. This is a qualitative-descriptive study that describes specific axes regarding the recent migration from Central America and the Caribbean in Baja California, as well as linguistic needs that the deported immigrants in the last months of 2017 due to the rigorous migration policy of President of the Unites States of America Donald J. Trump. On the other hand, this study describes the reality that deported and returned immigrants face toward this current situation. The result of this study reveals the linguistic emergence scenarios of immigrants who live at the border region and specifically the role of the languages in the new immigrants of Baja California.